Β-2-Himachalen-6-ol inhibits 4T1 cells-induced metastatic triple negative breast carcinoma in murine model. (25th August 2019) - Daaboul, Hamid E.; Dagher, Carole; Taleb, Robin I.; Bodman-Smith, Kikki; Shebaby, Wassim N.; El-Sibai, Mirvat; Mroueh, Mohamad A.; Daher, Costantine F.
Abstract: β-2-himachalen-6-ol (HC), a major sesquiterpene isolated from the Lebanese wild carrot umbels, was shown to possess remarkable in vitro and in vivo anticancer activities. The present study investigates the anti-metastatic activity of HC post 4T1 breast cancer cells inoculation in a murine model. The effect of HC on 4T1 cell viability was assessed using WST-1 kit, while cell cycle analysis was performed using flow cytometry. Tumor development and metastasis were evaluated by injecting 4T1 cells in the mice mammary gland region followed by either HC or cisplatin treatment. The 6-thioguanine assay was used for the quantification of metastatic cells in the blood. HC treatment caused a dose-dependent decrease in cell viability with IC50 and IC90 values of 7 and 28 μg/mL respectively. Concomitant treatment with cisplatin significantly reduced cell viability when compared to cells treated with cisplatin or HC alone. Flow cytometry revealed a significant increase ( p ˂0.05) in cell count in the Sub-G1 phase at HC 10 μg/mL, and total DNA fragmentation ( p ˂0.001) at HC 25 μg/mL. Annexin/PI staining showed early and late apoptotic mode of cell death upon treatment with HC. Histopathological evaluation revealed less incidence of primary and metastatic tumor/inflammation in the HC and cisplatin treated groups. Tumor size and colony-forming units were significantly decreased in the HC treated group. HC treatment induced cell cycle arrest, promoted apoptosis and reduced the incidence of primary and metastatic lesions caused by 4T1 cells. The present findings suggest that HC has an anti-metastatic potential against aggressive types of cancer. Highlights: β-2-himachalen-6-ol (HC) causes a dose-dependent decrease in cell viability. Concomitant treatment with cisplatin significantly reduced cell viability. HC induces cell cycle arrest and promotes apoptosis. HC reduces the incidence of primary and metastatic tumors. HC decreases tumor size and colony-forming units.